Microbiome species diversity and seasonal stability of two temperate marine sponges Hymeniacidon perlevis and Suberites massa - Claire E. Lamb; Joy E. M. Watts (Environmental Microbiome, 2023)
Abstract Background Marine sponges are diverse and functionally important members of marine benthic systems, well known to harbour complex and abundant symbiotic microorganisms as part of their species-specific microbiome. Changes in the sponge microbiome have previously been observed in relation to natural environmental changes, including nutrient availability, temperature and light. With global climate change altering seasonal temperatures, this study aims to better understand the potential effects of natural seasonal fluctuations on the composition and functions of the sponge microbiome. Results Metataxonomic sequencing of two marine sponge species native to the U.K. (Hymeniacidon perlevis and Suberites massa) was performed at two different seasonal temperatures from the same estuary. A host-specific microbiome was observed in each species between both seasons. Detected diversity within S. massa was dominated by one family, Terasakiellaceae, with remaining dominant families also being detected in the associated seawater. H. perlevis demonstrated sponge specific bacterial families including aforementioned Terasakiellaceae as well as Sphingomonadaceae and Leptospiraceae with further sponge enriched families present. Conclusions To our knowledge, these results describe for the first time the microbial diversity of the temperate marine sponge species H. perlevis and S. massa using next generation sequencing. This analysis detected the presence of core sponge taxa identified in each sponge species was not changed by seasonal temperature alterations, however, there were shifts observed in overall community composition due to fluctuations in less abundant taxa, demonstrating that microbiome stability across seasons is likely to be host species specific.